Promising Techniques for Wastewater Treatment and Water Quality Assessment 2021
DOI: 10.5772/intechopen.93429
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Method of Ion Exchange Resins Regeneration and Its Optimization for Water Treatment

Abstract: Ion exchange membranes, specifically resin technology, lie at the heart of electrolytically conductive systems used in the treatment of wastewater. This chapter deals with ion exchange deionization and the effect of resin amount as well as the concentration of acid and base on the product conductivity. The strong acidic cation polymeric exchanger resin is commercially called MERCK 104765 cation exchanger IV with capacity greater than 3.2 mmol/ml, while the strong basic anion polymeric exchanger resin is commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
5
0
2
Order By: Relevance
“…Thus, it can be concluded that regenerating with 5% NaOH performed better than 4% NaOH, presumably, by enabling the recovery of active sites. It has been observed that the regeneration process allows recovery of about 60–80% of the resin capacity, 19 which agrees with our results. The reason for the decrease in %FFA adsorption can be attributed to the inefficient generation of active sites as well as loss of resin particle size and sphericity.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, it can be concluded that regenerating with 5% NaOH performed better than 4% NaOH, presumably, by enabling the recovery of active sites. It has been observed that the regeneration process allows recovery of about 60–80% of the resin capacity, 19 which agrees with our results. The reason for the decrease in %FFA adsorption can be attributed to the inefficient generation of active sites as well as loss of resin particle size and sphericity.…”
Section: Resultssupporting
confidence: 92%
“…Ion‐exchange resin are susceptible to chemical or physical deactivation or neutralization of their active sites 18 . However, an advantage of using resins is the ability to recover their ion‐exchange capabilities by using regenerants, 19 so that they can be reused for multiple cycles. For Amberlite FPA51, the manufacturer recommends regenerating with 4% NaOH for a minimum of 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Pertukaran ion adalah pertukaran stoikiometri reversible ion antara fase padat (resin) dengan larutan, biasanya resin sebagai penukar ion tidak larut dalam media dimana pertukaran ion terjadi [7]. Pertukaran ion bisa secara efektif menghilangkan Natrium, Klorida, Kalsium, Magnesium dan ion lainnya untuk menghasilkan air murni yang dibutuhkan oleh industri.…”
Section: Reaksi Pertukaran Ion Pada Mixed Bedunclassified
“…Estas tienen un ion movible con carga positiva. Por su parte, las aniónicas poseen una carga negativa [31]. Además, durante su regeneración suelen someterse a diluciones de bases o ácidos fuertes [32].…”
Section: Resinas De Intercambio Iónicounclassified